Role of BP*C@AgNPs in Bap-dependent multicellular behavior of clinically important methicillin-resistant Staphylococcus aureus (MRSA) biofilm adherence: A key virulence study. (October 2018) - Zhang, Xu; Manukumar, H.M.; Rakesh, K.P.; Karthik, C.S.; Nagendra Prasad, H.S.; Swamy, S. Nanjunda; Mallu, P.; Eissa Mohammed, Yasser Hussein; Qin, Hua-Li
Abstract: Bacterial adhesion is a threshold event in the formation of biofilms which leads to serious bacterial diseases. This shows that the underlining the problem is interesting and need to solve the problem of biofilm-related complications. To support this, in the present study, we first time initiated to understand the role of methicillin-resistant Staphylococcus aureus (MRSA) biofilm using previously developed benzodioxane midst piperazine decorated chitosan silver nanoparticles (BP*C@AgNPs). The BP*C@AgNPs studied for antimicrobial, anti-biofilm, biofilm adherence inhibition, the role of ions in biofilm, and an antibiotic cocktail in the treatment of biofilm was assessed. The results showed that, the significant biocidal role of BP*C@AgNPs in controlling the MRSA biofilm and interaction of biofilm protein to calcium ions were significantly decreased. This confirms that calcium ion involved in the biofilm formation and for the treatment of BP*C@AgNPs, cocktail of enzyme and antibiotic have the promising therapeutic value was observed. In future the locking of biofilm protein and its expression in presence of calcium ion was interesting, and greater application related to biofilm infection was warrantable. Graphical abstract: Highlights: Synthesized BP*C@AgNPs acting as an antibiofilm candidate. The biofilm of MRSA is Ca 2+ and extracellular polysaccharide dependent. Ruled out the cocktail of treatment beneficiary for the drug resistant pathogens. Regulation of biofilm dependent protein in the Ca 2+ presence, appreciate the future application in antibiofilm therapy.